Perilaku Riba Kebiasaan Masyarakat Sesat Tidak Sesuai Prinsip-prinsip Syariah Islam - Herlina Kusuma Wardani (ITB AAS INDONESIA Surakarta, 2017)
Usury is an income gained arbitrarily or unfairly from one party to another. Riba in outline is divided into two, namely usury nasi'ah and usury fadhl. The human habit that makes usury is a belief that is not only perverted, but besides heresy is also misleading. A person who behaves in usury means clearly and openly as an opponent of Allah azza wajalla and Rasulullah SAW. Truly hostile to Allah and His Messenger will be a major step in Shaitan's deviance of men. Allah SWT and Rasulullah SAW will also openly combat the behavior of usury. The behavior of usury is not compatible with the principles of Islamic sharia. Even because the behavior of usury and misleading, so that the adzab Allah will be inflicted not only to the perpetrators of usury, but people who do not do it if living in a society that behaves in usury affected adzab